Leadership in Action : Issues and Observation--Taking the Balcony View - Manoogian, Sam (Center for Creative Leadership, 2009)
The ability to step back, see all the action, and take an objective view of events, rather than a subjective, emotional, tunnel-vision perspective, is essential to effective action and may be the most important skill of all for leaders.